2022
DOI: 10.1186/s12936-022-04217-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cone bioassay estimates at two laboratories with different Anopheles mosquitoes for quality assurance of pyrethroid insecticide-treated nets

Abstract: Background Quality assurance (QA) of insecticide-treated nets (ITNs) delivered to malaria-endemic countries is conducted by measuring physiochemical parameters, but not bioefficacy against malaria mosquitoes. This study explored utility of cone bioassays for pre-delivery QA of pyrethroid ITNs to test the assumption that cone bioassays are consistent across locations, mosquito strains, and laboratories. Methods Double-blinded bioassays were conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 73 publications
(104 reference statements)
0
26
0
Order By: Relevance
“…farauti mosquitoes in PNG when new, used in the field and also after 25 washes [ 5 ]. This was further confirmed in independent repetitions of the bioassays with different mosquito colonies [ 5 , 10 ]. Despite this, both types of PermaNet ® 2.0 (FC-coated and non-FC-coated) contained similar amounts of deltamethrin, meaning that bioefficacy was affected by the coating formulation change only, leading to a completely altered LLIN product with a significantly inferior ability to kill susceptible An.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…farauti mosquitoes in PNG when new, used in the field and also after 25 washes [ 5 ]. This was further confirmed in independent repetitions of the bioassays with different mosquito colonies [ 5 , 10 ]. Despite this, both types of PermaNet ® 2.0 (FC-coated and non-FC-coated) contained similar amounts of deltamethrin, meaning that bioefficacy was affected by the coating formulation change only, leading to a completely altered LLIN product with a significantly inferior ability to kill susceptible An.…”
Section: Discussionmentioning
confidence: 60%
“…Despite this, both types of PermaNet ® 2.0 (FC-coated and non-FC-coated) contained similar amounts of deltamethrin, meaning that bioefficacy was affected by the coating formulation change only, leading to a completely altered LLIN product with a significantly inferior ability to kill susceptible An. farauti and Anopheles gambiae (Ifakara) colony mosquitoes [ 5 , 10 ]. During the coating process, a polymer film forms around the polyester fibres and the insecticide crystals are bound in the polymer coating.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…farauti mosquitoes in PNG when new, used in the eld and also after 25 washes [5]. This was further con rmed in independent repetitions of the bioassays with different mosquito colonies [5,9]. Despite this, both types of PermaNet® 2.0 (PFC and non-PFC) contain similar amounts of deltamethrin, meaning that bioe cacy was affected by the coating formulation change only.…”
Section: Discussionmentioning
confidence: 85%
“…It was also suspected that the mosquito strain that we had used (a fully pyrethroid susceptible strain of Anopheles farauti) or technicalities related to conducting WHO cone bioassays at the PNG Institute of Medical Research were responsible for the observed inferior LLIN performance. We ruled out these possibilities categorically, by conducting a multi-centre trial with the same LLIN samples, which showed that our observations were reproducible in an African 'Good Laboratory Practice' accredited facility [9].…”
Section: Introductionmentioning
confidence: 99%